Turnover and promotion of lawyers: an inquiry into gender differences. - Spurr, Stephen J.; Sueyosji, Glenn T. (Journal of Human Resources)
This paper analyzes the turnover and promotion of male and female lawyers, using data on two cohorts of lawyers; one which entered law firms between 1969 and 1973, and the other entering between 1980 and 1983. This study considers whether law firm promotion decisions have differed for women, and if so, whether these differences have declined over time. A competing risks duration model is employed to capture the link between the lawyer's decision to stay or leave and the firm's decision to grant or deny promotion. We find that over the entire sample period, women are considerably less likely to be promoted and slightly more likely to leave the firm without being promoted. However, we also find that the parametric differential between men and women in partnership hazards has been reduced substantially, and in the most general of our specifications, eliminated across the two cohorts. In contrast, the gap between male and female job turnover rates does not appear to change over time. We find that the gap between males and females in the cumulative partnership rate at seven years of experience falls from 32 to 14 percent. The turnover gap increases about 0.2 percent, with females slightly more likely to exit from the firm in the later period. Reprinted by permission of the publisher.